Cannabis-Based Products in a Neurological Setting: A Clinical and Pharmacokinetic Survey - Mohamed, Susan; Lopane, Giovanna; Sabattini, Loredana; Scandellari, Cinzia; Zardi, Diletta; Donadio, Vincenzo; Rizzo, Giovanni; Perrone, Alessandro; Lugaresi, Alessandra; Contin, Manuela (Frontiers in Neurology, 2022)
Background and aim: Limited data are available in clinical settings on the pharmacokinetics of delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). We investigated the use of cannabis-based products in neurological practice, monitoring patients’ steady-state cannabinoids plasma concentrations matched with different preparations. Methods: This was a prospective, single-center, observational study. Patients underwent venous blood withdrawal before the cannabinoids’ morning dose, and then 2.5 hours post dosing. Spasticity or pain were patient self-assessed by the Numeric Rating Scale (NRS) before the morning cannabinoids administration and 2.5 hours post dosing. Results: Thirty-three patients were enrolled. Main indications for cannabinoids were spasticity and chronic pain. Sixteen patients were treated with oromucosal spray formulation and 17 with oil-based solutions. Both cannabinoids’ trough plasma concentrations were ≤ limit of detection (0.1 ng/ml) in 45% of patients. Intrasubject cannabinoids’ plasma levels significantly increased over baseline values in patients treated with Bediol® oil (p<0.05) and Sativex® (p<0.01). Post-dosing CBs bioavailability did not significantly differ between oral oil and oromucosal spray. NRS scores decreased (p<0.01), matching the increase (p<0.01) in cannabinoids plasma concentrations. Conclusion: This is the first study investigating cannabinoids plasma concentrations of oral and oromucosal preparations in real-world neurological practice. Findings of similar bioavailability for both CBD and THC after galenic oil compared with oromucosal spray dosing may be clinically relevant and deserve additional research in larger cohorts.